Analysis of Students Response Toward the Implementation of Round Table Technique in Writing for General Communication Course - Aseptiana Parmawati; Iman Santoso (Jurnal Pendidikan Edutama, 2021)
AbstrakWriting  is  also  a  productive  talent which  is  meant for  communication  to  deliver  messages in  the  shapesvof  letters  and  symbols. In the course of writing for general communication, students are expected to be able to write using several genre of text. Round Table is one of teaching technique which is implemented by cooperative learning approach. The specific purpose of this study is to prove the students responses toward Round Table techniques in improving writing skills in the Writing for General Communication course. This research used a descriptive qualitative. The research conducted in the second semester students at IKIP Siliwangi in the academic year of 2019/2020. Purposive sample is the technique that the researchers taken. The subject of this research consist of 48 students. Questionnaire grid used as instrument in this research. After analyzing the data descriptively, the results show that all of the students were actively involved during the teaching and learning activity. They have a high motivation to learn. The students understand the material easier. The learning process is interesting and not boring. They are motivated to get good achievement because they feel more valued in expressing opinions when learning. Keyword: Response, Writing, Round Table Technique AbstrakMenulis merupakan keterampilan produktif yang dimaksudkan untuk berkomunikasi guna menyampaikan pesan dalam bentuk huruf dan simbol. Dalam mata kuliah Writing for General Communication, siswa diharapkan dapat menulis menggunakan beberapa jenis teks. Round Table adalah salah satu teknik pengajaran yang dapat diimplementasikan dengan pendekatan pembelajaran yang bersifat kooperatif. Tujuan khusus dari penelitian ini adalah untuk dapat mengetahui bagaiman tanggapan mahasiswa terhadap penggunaan teknik Round Table dalam meningkatkan keterampilan menulis dalam mata kuliah Writing for General Communication. Penelitian ini merupakan penelitian deskriptif kualitatif. Penelitian ini dilaksanakan pada mahasiswa semester kedua di IKIP Siliwangi pada tahun akademik 2019/2020. Purposive sample adalah teknik pengambilan sampek yang digunakan oleh peneliti. Subjek penelitian ini terdiri dari 48 siswa. Kuisioner digunakan sebagai instrumen dalam penelitian ini. Setelah menganalisis data secara deskriptif, hasilnya menunjukkan bahwa semua siswa terlibat aktif selama kegiatan belajar mengajar. Mereka memiliki motivasi belajar yang tinggi. Siswa lebih mudah memahami materi. Proses pembelajarannya menarik dan tidak membosankan. Mereka termotivasi untuk mendapatkan prestasi yang baik karena mereka merasa lebih dihargai dalam mengekspresikan pendapat saat belajar  Kata kunci: Respon, Menulis, Teknik Round Table